The Effect of Green Organizational Culture and Green Innovation in influencing Competitive Advantage and Environmental Performance - Roeshartono Roespinoedji; Mohd Haizam Mohd Saudi; Andhika Ligar Hardika; Aimi Zulhazmi Abdul Rashid (International Journal of Supply Chain Management, 2019)
The preset study investigated the role of green organizational culture as the antecedent of both green product and process innovation. In addition, the current examination also analyzed the unique contribution of both product and process innovation in prompting organizational competitiveness and environmental performance in Malaysian companies. In doing so, we apply Partial Least Square equation modeling approach. The results of the examination confirm that green product innovation, green process innovation and competitive advantage have positive and significant influenced by green organizational culture. Moreover, the results of PLS-SEM likewise confirm that competitive advantage is positive and significantly influenced by green product innovation and green process innovation. The outcomes further affirm that competitive advantage has positively and significantly impact on environmental performance in Malaysian manufacturing firms.